Bioorthogonal mimetics of palmitoyl‐CoA and myristoyl‐CoA and their subsequent isolation by click chemistry and characterization by mass spectrometry reveal novel acylated host‐proteins modified by HIV‐1 infection. Issue 12 (26th May 2015) - Colquhoun, David R.; Lyashkov, Alexey E.; Mohien, Ceereena Ubaida; Aquino, Veronica N.; Bullock, Brandon T.; Dinglasan, Rhoel R.; Agnew, Brian J.; Graham, David R. M.; Cristea, Ileana M.; Graham, David
<x xml:space="preserve">Abstract</x> Protein acylation plays a critical role in protein localization and function. Acylation is essential for human immunodeficiency virus 1 (HIV‐1) assembly and budding of HIV‐1 from the plasma membrane in lipid raft microdomains and is mediated by myristoylation of the Gag polyprotein and the copackaging of the envelope protein is facilitated by colocalization mediated by palmitoylation. Since the viral accessory protein NEF has been shown to alter the substrate specificity of myristoyl transferases, and alter cargo trafficking lipid rafts, we hypothesized that HIV‐1 infection may alter protein acylation globally. To test this hypothesis, we labeled HIV‐1 infected cells with biomimetics of acyl azides, which are incorporated in a manner analogous to natural acyl‐Co‐A. A terminal azide group allowed us to use a copper catalyzed click chemistry to conjugate the incorporated modifications to a number of substrates to carry out SDS‐PAGE, fluorescence microscopy, and enrichment for LC‐MS/MS. Using LC‐MS/MS, we identified 103 and 174 proteins from the myristic and palmitic azide enrichments, with 27 and 45 proteins respectively that differentiated HIV‐1 infected from uninfected cells. This approach has provided us with important insights into HIV‐1 biology and is widely applicable to many virological systems.